Study of Electrochemical Impedance of a Continuous Glucose Monitoring Sensor and its Correlation with Sensor Performance - Sanjiv Sharma (IEEE Sensors Letters, 2017)
In this work, we study the change in the sensitivity and the electrochemical impedance of continuous glucose monitoring sensors over time. 28-day sensitivity and EIS measurement results on four similar sensors are presented. The sensitivity of the sensor is observed to be related to its double-layer capacitance and charge-transfer resistance, based on results acquired from a sensor that showed substantial sensitivity drop. Two data clusters are extracted that relate the sensor sensitivity to its impedance before and after the sensitivity drops by more than 50%.